2011
DOI: 10.1148/radiol.11102338
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Shock in Polytrauma Patients: Early Detection with Renal Doppler Resistive Index Measurements

Abstract: In polytrauma patients who are hemodynamically stable at admittance to the ED, renal cortical blood flow redistribution occurs very early in response to occult bleeding and might be noninvasively detected by using the renal Doppler RI. A renal Doppler RI greater than 0.7 is predictive of progression to hemorrhagic shock in polytrauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 42 publications
(33 reference statements)
1
42
0
Order By: Relevance
“…There is a general consensus about a cutoff range of RRI 0.70÷0.74 to define patients exposed to a significant risk of AKI or other adverse events after major surgery (10,11). In our sample the median value was a little lower (RRI 0.68) than the cutoff.…”
Section: Discussionmentioning
confidence: 76%
“…There is a general consensus about a cutoff range of RRI 0.70÷0.74 to define patients exposed to a significant risk of AKI or other adverse events after major surgery (10,11). In our sample the median value was a little lower (RRI 0.68) than the cutoff.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies have shown the usefulness of RRI to predict the occurrence and severity of AKI in critically ill patients. Corradi et al showed that the RRI is altered in patients with haemorrhagic shock [36], while in critically ill patients it has been shown to be clinically useful in order to predict the reversibility of AKI [37]. An improvement of RRI has also been demonstrated after an increase of MAP with noradrenaline in septic shock patients [38].…”
Section: Rri = Peak Systolic Velocity -End Diastolic Velocity Peak Symentioning
confidence: 99%
“…The use of such modalities as the renal or splenic Doppler resistance index in trauma is promising for identifying those patients at the bedside, but these modalities will need further confirmation in critically ill patients. 39,40 Dynamic variables are most useful in finding the patient's individual point on the Frank-Starling curve.…”
Section: Dynamic Variablesmentioning
confidence: 99%